Home-range size, response to fire, and habitat preferences of wintering Henslow's Sparrows - Bechtoldt, Catherine L.; Stouffer, Philip C. (Wilson Bulletin, 2005)
Henslow's Sparrow (Ammodramus henslowii) is a declining, disturbance-dependent grassland bird that winters in the longleaf pine (Pinus palustris) ecosystem of the southeastern United States. During two winters (2001, 2002), we estimated the relative abundances, movement patterns, and habitat associations of Henslow's Sparrows wintering in habitat patches differing in time since last burn (burn treatment). We conducted our study in southeastern Louisiana in Andropogon spp.-dominated longleaf pine savanna habitat. Henslow's Sparrows were most abundant in savannas burned the previous growing season, with a mean relative abundance of 2.6 individuals/ha. The most dramatic decline occurred between burn year 0 and year 1 (first and second winters after burning), when mean relative abundance dropped to 1.0 individual/ha. Home-range size of radio-tagged birds was not correlated with burn treatment. All radio-tagged individuals maintained stable home ranges, with a mean size of 0.30 ha. Vegetation characteristics differed significantly among burn treatments. Sites burned the previous growing season had low vegetation density near the ground, vegetation taller than 1.0 m, and high seed abundance. These variables were all highly correlated with Henslow's Sparrow relative abundance, but seed density best predicted Henslow's Sparrow numbers. We recommend a biennial, rotational burn regime to maintain habitat characteristics correlated with Henslow's Sparrow abundance.
Keywords: Burning; Habitat Selection; Home Range; Movement; Overwintering; Passerine; Range Size; Relative Abundance; Louisiana; North America; United States; Western Hemisphere; World; Ammodramus Henslowii; Andropogon; Aves; Passeridae; Pinus Palustris